Occupational asthma in a mineral analysis laboratory. Issue 6 (June 1988) - Musk, A W; Peach, S; Ryan, G
Abstract : An epidemic of symptoms suggestive of occupational asthma in workers in a mineral analysis laboratory necessitating exposure to vapours of hydrochloric, hydrofluoric, nitric, perchloric, and sulphuric acid solutions was investigated. Variable airflow obstruction was confirmed by serial measurement of FEV1 in two subjects who showed 18% and 22% fall in FEV1 during a workshift. Of a workforce of 21 laboratory staff, 20 took part in a study of ventilatory capacity and bronchial reactivity. All but one subject had normal ventilatory capacity but five had bronchial hyperreactivity (PC20 less than or equal to 8 mg/ml histamine). Four of the five with hyperreactivity had a history of chest tightness at work whereas only two subjects with chest tightness had PC20 greater than 8 mg/ml (p less than 0.01). Other work related symptoms were cough (two subjects) and breathlessness (three subjects). Four of the subjects with bronchial hyperreactivity were atopic, suggesting that hyperreactivity may have predated exposure to irritant material at work and resulted in their being susceptible to the development of symptoms and raises the possibility of identifying susceptible subjects by preplacement examination. In two of these subjects, however, bronchial reactivity has returned to normal after 205 and 376 days away from work, suggesting that bronchial inflammation resulted from occupational exposure to acid vapours.